Modelagem matemática para otimização do planejamento e programação da produção em uma fundição de pequeno porte - BERTULUCCI, Michael Ferreira (2017)
The current economic scenery of falling demand of fused materials reinforces the need for innovation in the production process to keep the competitiveness of the foundries. The present work analyzes the main mathematical models found in the literature for the lot sizing and alloy sequencing in market foundries and proposes an extension for multiple alternative furnaces in a small foundry. The focus of the analyzed models is the reduction of the costs of delay, stock and furnace preparation. The choice of the model was made based on the objective function, gap and underutilization of the furnace given by computational tests. For the development of this work, the process of planning the production of a foundry was studied in loco with data collection and questionnaire application for validation procedure. Production plans with significantly better performance than those made by the company were presented and validated. The model was validated, however, not implemented due to the inherent costs of acquisition of the optimization software.